Pengaruh Neuromuscular Taping Dan Contract Relax Stretching Pada Kondisi Myofascial Pain Syndrome Otot Upper Trapezius Terhadap Penurunan Nyeri Leher - Sari Triyulianti (LPPM Universitas Abdurrab, 2022)
ABSTRACT Background: Myofacial trigger point syndrome of the upper trapezius muscle is pain in a hyperirritable point/place in the muscle or fascia caused by trauma or loading due to continuous muscle work. Muscles that work excessively will cause continuous contractions which will cause tense, causing spasms, stiffness, adhesions and decreased blood circulation which triggers the emergence of trigger points in tense muscles. This condition is found in all people with unergonomic position for long periods of time in the neck area, especially the upper trapezius muscle which is often found to be excessively contracted, maintaining a head posture that tends to fall forward due to the force of gravity or the weight of the head. Excessive contraction triggers the emergence of trigger points in the link band which causes myofascial pain syndrome so that it will have an impact on neck pain. The purpose of this study was to determine the effect of neuromuscular taping and contract relax stretching on myofascial pain syndrome of the upper trapezius muscle on reducing neck pain. Methods: This study used an experimental method with a pre and post test design on 14 people who were taken randomly according to the inclusion criteria and exclusion criteria. The intervention is neuromuscular taping and contract relax stretching. Pain measurements were measured using a visual analog scale (VAS). The data is processed and analyzed with the SPSS 21. Results: The results of the hypothesis test were obtained with p = 0.000 meaning p <0.05, so there was an effect of neuromuscular taping and contract relax stretching on neck pain in myofascial pain syndrome of the upper trapezius muscle. Conclusion: The results of this study indicate that neuromuscular taping and contract relax stretching can reduce neck pain in myofascial pain syndrome of the upper trapezius muscle.